The Influence Of Islamic Religious Education Learning In Improving Students' Social Skills At State Vocational School 1 Cugenang - Cep Ramdan Hidayat; Deden Rohandi; Maharani Muria (Doctoral Program of Social Science Pasundan University, 2026)
Islamic religious education learning is the main pillar in instilling moral values ??and social ethics that underlie students' social skills. This study aims to determine 1) the implementation of Islamic religious education learning; 2) the reality of students' social skills; 3) the influence between Islamic religious education learning in improving students' social skills. The research method used is quantitative research method, with a correlational approach. The population in this study were all students of SMK Negeri 1 Cugenang which amounted to 568 people and the number of samples was 57 respondents. The sampling technique used was simple random sampling. The data collection techniques used are questionnaires, observations and interviews. The implementation of Islamic religious education learning obtained a score of 86% of the expected ideal score. The reality of students' social skills scored 84% of the expected ideal score. The t test results obtained sig value. 0.000 < 0.05, meaning that there is a significant influence between Islamic religious education learning in improving students' social skills. This is indicated by the results of quantitative data and reflective student attitudes. The results of the determination coefficient test (R Square) obtained a value of 0.461 or 46.1%, which means that the percentage of the influence of Islamic religious education learning on student social skills is 46.1%.